KINERJA PENGELOLAAN LIMBAH HOTEL PESERTA PROPER DAN NON PROPER DI KABUPATEN BADUNG, PROVINSI BALI - Putri Nilakandi Perdanawati Pitoyo; I Wayan Arthana; I Made Sudarma (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2016)
Bali tourism development can lead to positive and negative impacts that threatening environmental sustainability. This research evaluates the hotel performance of the waste management that includes management of waste water, emission, hazardous, and solid waste by hotel that participate at PROPER and non PROPER. Research using qualitative descriptive method. Not all of non PROPER doing test on waste water quality, chimney emissions quality, an inventory of hazardous waste and solid waste sorting. Wastewater discharge of PROPER hotels ranged from 290.9 to 571.8 m3/day and non PROPER ranged from 8.4 to 98.1 m3/day with NH3 parameter values that exceed the quality standards. The quality of chimney emissions were still below the quality standard. The volume of the hazardous waste of PROPER hotels ranged from 66.1 to 181.9 kg/month and non PROPER ranged from 5.003 to 103.42 kg/month. Hazardous waste from the PROPER hotel which has been stored in the TPS hazardous waste. The volume of the solid waste of PROPER hotel ranged from 342.34 to 684.54 kg/day and non PROPER ranged from 4.83 to 181.51 kg/day. The PROPER and non PROPER hotel not sort the solid waste. The hotel performance in term of wastewater management, emission, hazardous, and solid waste is better at the PROPER hotel compared to non PROPER participants.